The Relevance of Maulana Saeed Nursi's Thoughts in Responding to the Global Crisis Through the Qur'an - Muhammad Juni Beddu; Muhammad Faisal; Muhammad Zakir Husain; Hazem Mamoun; Ita Tryas Nur Rochbani (RUSYDIAH: Jurnal Pemikiran Islam, 2025)
Global contemporary crises, including moral degradation, spiritual disorientation, environmental crises, and humanitarian conflicts, indicate the disconnection of modern humanity from transcendental values. In this context, the thought of Badiuzzaman Said Nursi (1877–1960) is examined as an alternative Qur’anic-based solution. This study aims to thematically analyze the relevance of Nursi’s ideas in Risalah Nur to modern global problems. The research employs a library research method with a qualitative-descriptive approach, using thematic analysis of the main texts of Risalah Nur and relevant secondary sources. The findings reveal three main points. First, the concept of rational faith in Risale-i Nur is operationalized through logical-empirical arguments that function as a foundation for strengthening spiritual awareness in confronting secularism. Second, the integration of revelation and reason is demonstrated through an epistemological framework that positions science as a means of contemplation (tafakkur), rather than as an entity opposed to religion. Third, the concepts of ukhuwah insaniyah and the ethics of tawhid generate principles of social and ecological responsibility reflected in the call to maintain harmony between humanity and nature. The contribution of this study lies in formulating a conceptual framework connecting rational faith, the integration of religion and science, and socio-ecological ethics within a thematic perspective based on Risalah Nur. This study highlights its novelty by asserting that the internalization of Qur’anic values through the rational and spiritual approach formulated by Nursi remains highly relevant for building a just civilization oriented toward balance between material and spiritual dimensions.